PERAN KESENIAN SARAFAL ANAM DALAM MENINGKATKAN NILAI MORALITAS PEMUDA - Fadhilah, Ana; Zuky, Heru; Efendi, Sutrian; Purwanti, Diyah; Septiady, Agil (CV. Kalimasada Group, 2024)
Humans are cultural creatures. Through reason, humans can develop culture. Likewise, humans live and depend on culture as a result of their creation. Therefore, culture has a big function for humans and society. Air Periukan Village is one of the villages in Bengkulu Province. The people of Air Periukan Village are rich in oral culture and literature. Sarafal Anam performing arts is one of the cultures of the people of Air Periukan Village which is still alive in the community. It should be noted that the Sarafal Anam performance culture owned by the people of Air Periukan Village, based on the results of data analysis and discussion, the author concludes that the Sarafal Anam art performance for the people of Air Periukan Village has a role as a place of expression for the community, especially the youth in Air Village. This is an impact that has an impact on increasing self-confidence by having the courage to appear, a sense of responsibility to preserve art and culture, akhlakul kharimah by imitating the attitude of the Prophet and becoming a barrier to despicable attitudes that are rampant among young people today such as promiscuity, brawls, illegal racing, gambling and other things that can disturb peace. Through the Sarafal Anam performing arts, which also contain the values of solidarity and togetherness, they will always be well fostered. Especially for youth in Air Periukan Village.